2001
DOI: 10.1046/j.1365-2222.2001.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

An open audit of montelukast, a leukotriene receptor antagonist, in nasal polyposis associated with asthma

Abstract: The findings are consistent with a subgroup of nasal polyps/asthma patients in whom leukotriene receptor antagonists are effective. This is not related to aspirin sensitivity. Further placebo-controlled studies need to be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 37 publications
3
76
0
4
Order By: Relevance
“…They identified 5 such studies. Three were RCTs (level 1b), 1043,1046,1047 with 1 each of a nonrandomized, noncontrolled study (level 3) 1048 and a basic science study (level 5). 1049 Overall, they found moderate evidence of efficacy as an adjunctive treatment, used in conjunction with corticosteroids.…”
Section: Viiie9 Crswnp Management: Anti-lt Therapymentioning
confidence: 99%
“…They identified 5 such studies. Three were RCTs (level 1b), 1043,1046,1047 with 1 each of a nonrandomized, noncontrolled study (level 3) 1048 and a basic science study (level 5). 1049 Overall, they found moderate evidence of efficacy as an adjunctive treatment, used in conjunction with corticosteroids.…”
Section: Viiie9 Crswnp Management: Anti-lt Therapymentioning
confidence: 99%
“…Many patients require long-term oral glucocorticosteroids to achieve asthma control. Leucotriene receptor antagonists and synthesis inhibitors may also be of clinical benefit, although the magnitude of improvement after leucotriene antagonists did not seem to exceed that observed in ASA-tolerant patients (47). Management of chronic rhinosinusitis and nasal polyps (both medical and surgical if necessary) is essential, may be a prerequisite for the improvement of bronchial symptoms and should be conducted in close collaboration with the ENT specialist (22,48).…”
Section: Management Of a Patient With Aerdmentioning
confidence: 99%
“…Aspirin sensitivity was deduced from patients' histories and confirmed by lysine-aspirin nasal provocation, as previously described. 5 All patients also underwent skin prick tests with 10 common, inhaled allergens. Seven patients had positive reactions to house dust mite, pollen, grass, tree or cat antigens.…”
Section: Methodsmentioning
confidence: 99%
“…4 Our previous study, using the leukotriene D 4 receptor antagonist montelukast, confirmed the evidence that leukotrienes play an important role in the development of nasal polyps in patients with aspirin-intolerant asthma. 5 Trials of desensitisation, using aspirin, have been reported in patients with aspirin-intolerant asthma. Initially, the effect on asthma of oral desensitisation was examined.…”
Section: Introductionmentioning
confidence: 99%